Transformation of Islamic Religious Education Learning in High Schools in the Digital Era - Nur Rohman; Nur Cholid; M. Ahsanul Husna (Chalim Journal of Teaching and Learning, 2026)
The rapid development of digital technology has significantly transformed educational practices, including Islamic Religious Education (PAI) teaching in secondary schools. However, many PAI teaching processes still rely on conventional, teacher-centered approaches that are less responsive to the characteristics of digital-generation students. This study aims to analyze the transformation of PAI teaching in senior high schools by examining pedagogical changes, digital technology integration, and character building in the learning process. This study used a qualitative approach with a case study design conducted in three secondary schools in Bojonegoro Regency, Indonesia. Participants consisted of PAI teachers, principals, and students selected through purposive sampling. Data were collected through in-depth interviews, classroom observations, and document analysis. The results show that the transformation of PAI teaching has gradually shifted toward student-centered learning through collaborative learning, reflective discussions, and contextual learning practices. The use of digital media such as interactive videos, online learning platforms, and multimedia presentations has also increased student engagement and motivation. In addition, character education has been integrated into learning through discussions on social ethics, digital literacy, and religious values in everyday life. However, several obstacles remain, including limited digital competency among teachers, uneven technological infrastructure, and resistance to pedagogical change. The novelty of this study lies in its integrated analysis of pedagogical transformation, the use of digital technology, and character education in Islamic Religious Education (IS) learning in secondary schools. This study contributes both theoretically and practically to the development of innovative and contextual Islamic education models in the digital era.